Synthesis of Methacrylate Monomers with Antibacterial Effects Against S. Mutans - Jingwei He; Monica Österblad; Pekka K. Vallittu; Lippo V. J. Lassila; Eva Söderling (Molecules, 2011)
A series of polymerizable quaternary ammonium compounds were synthesized with the aim of using them as immobilized antibacterial agents in methacrylate dental composites, and their structures were characterized by FT-IR, 1H-NMR, and 13C-NMR analysis. Their antibacterial activities against the oral bacterium Streptococcus mutans were evaluated in vitro by a Minimum Inhibitory Concentration test, and the results showed that 2-dimethyl-2-hexadecyl-1-methacryloxyethyl ammonium iodide (C16) had the highest antibacterial activity against S. mutans, and 2-dimethyl-2-pentyl-1-methacryloxyethyl ammonium iodide (C5) and 2-dimethyl-2-octyl-1-methacryloxyethyl ammonium iodide (C8) did not show any inhibition.